New Developments in Ocular Surface Squamous Neoplasia - Ayşe Yağcı (Türk Oftalmoloji Dergisi)
Ocular surface squamous neoplasia originates from conjunctiva epithelium and covers a broad spectrum of disease ranging from dysplasia to squamous cell carcinoma. Clinical features may vary from case to case. Traditional treatment of excision with no-touch technique combined with adjuvant therapies because of high recurrence rate. Main adjuvant treatments are cryotherapy and chemotherapy. In this review, clinical forms, differential diagnosis, American Joint Committee on Cancer classification and recent approaches to the management of ocular surface squamous dysplasia were described. (Turk J Ophthalmol 2014; 44: Supplement 8-14)